1999
DOI: 10.1111/j.1572-0241.1999.01208.x
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of Esophageal Motility With Age: A Manometric Study of 79 Healthy Subjects

Abstract: The results suggest that normal esophageal motility deteriorates with advancing age. Thus, age-related normality limits of esophageal pressures should be considered before establishing the manometric diagnosis of hypercontractile esophageal motility disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
57
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(69 citation statements)
references
References 29 publications
8
57
4
Order By: Relevance
“…Overall volume of the muscle tissue of the muscularis proper in the group of younger donors is larger than in the older group, but, again, the difference is not significant (less than 10%). This is in correlation with the findings of manometric studies that showed the lowering of the oesophageal peristaltic wave pressure with age [13,25]. The level of peristaltic wave reduction in their study is similar to the loss of overall muscle tissue volume that we found in the older group.…”
Section: Discussionsupporting
confidence: 91%
“…Overall volume of the muscle tissue of the muscularis proper in the group of younger donors is larger than in the older group, but, again, the difference is not significant (less than 10%). This is in correlation with the findings of manometric studies that showed the lowering of the oesophageal peristaltic wave pressure with age [13,25]. The level of peristaltic wave reduction in their study is similar to the loss of overall muscle tissue volume that we found in the older group.…”
Section: Discussionsupporting
confidence: 91%
“…2,3 Several studies showed decreased sphincter relaxations and decreased esophageal contraction and dilatation in the aged people. [4][5][6] The neural control of gastrointestinal function, including esophageal motility is related to enteric neurons. 7,8 It has been shown that changes in esophageal physiology is associated with loss of esophageal myenteric plexus neurons, which are part of the enteric nervous system (ENS) and lie within the smooth muscle layers of the esophageal wall in the aged population.…”
Section: Introductionmentioning
confidence: 99%
“…Others have noted that simultaneous contractions are more likely to occur in older than in younger patients [13,14] , especially in the presence of severe GORD [15] . The effect of age in relation to the occurrence of simultaneous contractions in healthy volunteers, however, remains unclear, as one study revealed no relationship between simultaneous contractions and age [16] , whereas a more recent study did find a direct correlation between the proportion of simultaneous contractions and age [17] . The most recent study revealed differences in muscle thickness between similarly-categorized IOM subsets, and a significant correlation between muscle thickness, and the occurrence of simultaneous contractions [14] .…”
Section: Discussionmentioning
confidence: 99%